154 Recurrence of angina after ST-elevation myocardial infarction: the role of microvascular obstruction. (May 2019) - Vetrugno, Vincenzo; Montone, Rocco A.; Fracassi, Francesco; Vergni, Federico; Russo, Michele; Del Buono, Marco G.; Santacroce, Giovanni; Camilli, Massimiliano; Gurguglione, Filippo L.; Meucci, M. Chiara; Niccoli, Giampaolo; Crea, Filippo
Abstract : Introduction: Recurrence of angina after percutaneous coronary intervention (PCI) affects 20–35% of patients with stable coronary artery disease. Few data are available in the setting of ST-segment elevation myocardial infarction (STEMI) treated with primary PCI and pathogenic mechanisms are largely unknown. In this study, we evaluated the relation between coronary microvascular obstruction (MVO) and recurrence of angina at follow-up. Methods: We prospectively enrolled patients with STEMI undergoing primary PCI. MVO was defined as TIMI flow <3 or TIMI flow 3 with myocardial blush grade <2. The primary endpoints were recurrence of angina at follow-up and angina status evaluated by Seattle Angina Questionnaire Summary Score (SAQSS). Therapy at follow-up and occurrence of major adverse cardiovascular events (MACE), defined as the composite of cardiac death, non-fatal myocardial infarction (MI) and target vessel revascularization (TVR), were also collected. Results: We enrolled 200 patients (66.5±11.3 years, male 75.5%). MVO occurred in 52 (26.1%) of them. Follow-up (mean time 25.17±9.28 months) was performed in all patients. Recurrent angina occurred in 29 (17.1%) patients, with a higher prevalence in patients with MVO compared with patients without MVO [11 (28.9%) vs 18 (10.6%); p=0.047]. Accordingly, SAQSS was lower in patients with MVO compared with patients without MVO, and the need of ≥2 antianginal drugs was higher in patients with MVO. Of note, at multiple linear regression analysis history of previous acute coronary syndrome and occurrence of MVO were the only independent predictors of a worse SAQSS (R2=0.089, p=0.001). Finally, occurrence of MACE [17 (32.7%) vs 25 (17%), p=0.028] was higher in patients with MVO compared with patients without MVO. Conclusion: Recurrence of angina in STEMI patients treated with primary PCI is an important clinical issue. Occurrence of MVO portends a worse angina status and is associated with the use of more antianginal drugs. Conflict of Interest: No conflict of interest